2012
DOI: 10.1249/mss.0b013e318247b324
|View full text |Cite
|
Sign up to set email alerts
|

Regular Maternal Exercise Dose and Fetal Heart Outcome

Abstract: Maternal physical activity dose during the third trimester is associated with resting fetal heart effects similar to a trained response. Future studies on the health benefits of this fetal response are highly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 38 publications
6
65
2
3
Order By: Relevance
“…Specifically, the intervention designed from the formative research reported here can be used to inform how physical activity messaging is incorporated into Text4-baby in the future. The current Text4baby curriculum has limited SMS about physical activity, and because the evidence supporting participation in physical activity as part of a healthy pregnancy is ample [1][2][3][4][5][6][7][8][9][10][11][12], there is a need to modify standard Text4baby physical activity SMS in light of these findings.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the intervention designed from the formative research reported here can be used to inform how physical activity messaging is incorporated into Text4-baby in the future. The current Text4baby curriculum has limited SMS about physical activity, and because the evidence supporting participation in physical activity as part of a healthy pregnancy is ample [1][2][3][4][5][6][7][8][9][10][11][12], there is a need to modify standard Text4baby physical activity SMS in light of these findings.…”
Section: Original Researchmentioning
confidence: 99%
“…For the mother, benefits may include weight control [4] and reduced risk of early delivery and gestational diabetes [2,3,[5][6][7], and for the fetus, benefits may include improved stress tolerance and a decrease in resting fetal heart rate [8][9][10][11][12]. Despite these benefits, only 15.8 % of pregnant women (as compared to 26 % of non-pregnant women) achieve recommendations for physical activity [6,13,14] (i.e., meeting physical activity recommendations of 150 min of moderate intensity activity per week) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The fetal heart adapts similar to the adult heart when exposed to exercise training. For example, fetuses of exercising women had improved cardiovascular autonomic control indicated by decreased heart rates and increased HRV, relative to those of non-exercisers [10,13]. Further analysis demonstrated a dose-response relationship, indicating that an increase in maternal exercise intensity and time spent participating in physical activity results in a greater fetal cardiovascular adaptation (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…The effects of aerobic exercise on maternal health have been long understood, with the body of research indicating the safety and efficacy of maternal exercise training regarding fetal and neonatal health is growing [1][2][3][4][5][6][7][8][9][10][11][12][13]. The fetus is not at risk of hypoxia or significant bradycardia during maternal exercise [4,9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation